(untitled) (Journal of Architectural Design, 2023)
The urban landscape primarily consists of residential buildings, making green sustainable buildings an effective strategy for shaping them. This study uses a descriptive methodology to investigate sustainable green buildings in residential structures, focusing on Gulf countries. Recommendations emphasize responsive design, adaptability to local climates, and materials, as well as prioritizing sustainable waste disposal and reuse programs.